Judicial decision in hostile environments: judges, executives, and the public in Argentina (2004-2010) - Pereira, JRG (2014)
The central argument of this work is that the level of aggression of judges sitting in vulnerable courts is a function of their attempt to protect the institutional security of such courts. I argue that in contexts characterised by a lack of a culture of judicial independence, by high levels of judicial delegitimisation, and a high level of public visibility of judicial affairs, judges will attempt to simultaneously construct public support and avoid political conflicts with the Government. As a result, judicial decisions are driven by judges’ calculations of both the public’s reaction and the Government’s reaction to their rulings. I claim the level of aggression of judges’ interventions will increase when the Government's tolerance to decisions against its preferences was is higher and the public appears to be more supportive. I empirically test this theory using the case of Argentine Supreme Court Justices between July 2004 and September 2010. The findings confirm the theoretical expectations according to which judges are simultaneously concerned with the construction of public support and the avoidance of conflicts with the Government. In addition, my study shows three relevant patterns in terms of judicial behaviour. First, the Justices increased their level of aggression by using different modes of involvement when the public appeared to be more supportive and the Government’s tolerance higher during the period under study. Second, the decreased level of aggression occurred by altering the features of the same remedy in response to the political conditions in which decisions were issued. Third, existing legal constraints prevented Justices from being more aggressive.